(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article analyzes the theoretical and practical aspects of physiotherapy and rehabilitation during pregnancy. It emphasizes the importance of supporting the musculoskeletal system, maintaining muscle tone, reducing excessive weight and edema, and preparing for childbirth. Various physiotherapeutic methods, exercises, massage, and hydrotherapy are examined.